Primary beam effects of radio astronomy antennas – II. Modelling MeerKAT L-band beams. Issue 2 (15th January 2021) - Asad, K M B; Girard, J N; de Villiers, M; Ansah-Narh, T; Iheanetu, K; Smirnov, O; Santos, M G; Lehmensiek, R; Jonas, J; de Villiers, D I L; Thorat, K; Hugo, B; et al.
ABSTRACT: After a decade of design and construction, South Africa's SKA-MID precursor MeerKAT has begun its science operations. To make full use of the widefield capability of the array, it is imperative that we have an accurate model of the primary beam of its antennas. We have taken available L -band full-polarization 'astro-holographic' observations of three antennas and a generic electromagnetic simulation and created sparse representations of the beams using principal components and Zernike polynomials. The spectral behaviour of the spatial coefficients has been modelled using discrete cosine transform. We have provided the Zernike-based model over a diameter of 10 deg averaged over the beams of three antennas in an associated software tool (EIDOS) that can be useful in direction-dependent calibration and imaging. The model is more accurate for the diagonal elements of the beam Jones matrix and at lower frequencies. As we get more accurate beam measurements and simulations in the future, especially for the cross-polarization patterns, our pipeline can be used to create more accurate sparse representations of MeerKAT beams.